Pengaruh Likuiditas, Solvabilita, Aktivitas Terhadap Rentabilitas Pada Bank Konvensional Yang Terdaftar Di Bursa Efek Indonesia - Putri Sari Nilam Cahaya; Siti Ruhana Dara (STREAMING, 2022)
This Study aims to be able to know and analyze the effect of liquidity, solvency, activities on profitability in conventional banks listed on the Indonesia Stock Exchange in 2015-2019. The population of this study are all conventional banks listed on the Indonesia Stock Exchange in 2015-2019. The number of samples of this study are 10 convensional bankslisted on the Indonesia Stock Exchange in 2015-2019 that meet the criteria for a complete and periodic quarterly financial report in 2015-2019. The analytical method used in this study is panel data regression analysis which was tested using Eviews version 9. The result of this study indicate that Liquidity, Solvency, Activities affects the rentability of conventional banks listed on the Indonesia Stock Exchange in 2015-2019.